International Practice of Human Rights as Legal Demand-Rights: A Critical Approach - Dávila, Johnny Antonio (The Age of Human Rights Journal, 2022)
Margaret Gilbert’s approach to human rights asserts that these are demand-rights that may be moral or legal. As legal rights, human rights result exclusively from an international practice in which States hold a leading position. This paper offers a critique of Gilbert’s prominent approach to conceptualising human rights as legal demand-rights. I hold here that her state-centric approach does not correctly represent the international practice of human rights and may reinforce the dominant role of States vis-à-vis the individual, which contradicts our contemporary understanding of human rights. If Gilbert’s approach is followed in the way she has proposed, the realisation of these rights could be even more difficult. Such outcome can be avoided by accepting the dual (legal and moral) nature of human rights.